2021
DOI: 10.1021/acschemneuro.0c00649
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration Profiles of Olfactory Epithelium after SARS-CoV-2 Infection in Golden Syrian Hamsters

Abstract: Olfactory dysfunction is one of the most frequent and specific symptoms of coronavirus disease 2019 (COVID-19). Information on the damage and repair of the neuroepithelium and its impact on olfactory function after COVID-19 is still incomplete. While severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causes the ongoing worldwide outbreak of COVID-19, little is known about the changes triggered by SARS-CoV-2 in the olfactory epithelium (OE) at the cellular level. Here, we report profiles of the OE aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 29 publications
10
75
0
Order By: Relevance
“…Second, structural instability may contribute to olfactory dysfunction. As in previous studies, most of the epithelium was desquamated, some cellular debris was present in the lumen [ 10 , 21 , 40 ], and three distinct layers were lost. Because SCs are responsible for epithelial stability, their infection and subsequent apoptosis may result in these changes.…”
Section: Discussionsupporting
confidence: 57%
“…Second, structural instability may contribute to olfactory dysfunction. As in previous studies, most of the epithelium was desquamated, some cellular debris was present in the lumen [ 10 , 21 , 40 ], and three distinct layers were lost. Because SCs are responsible for epithelial stability, their infection and subsequent apoptosis may result in these changes.…”
Section: Discussionsupporting
confidence: 57%
“…The current evidence favors alternative routes from the nose to the brain, at least in the acute phase (first two weeks) of infection. Since the viral load typically reduces rapidly within the first week of infection [94], the brain appears to be protected in the vast majority of cases with SARS-CoV-2 infection. We are concerned that studies advocating an olfactory route for SARS-CoV-2 to infect the brain may unnecessarily alarm a large number of patients suffering from anosmia.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 invades the peripheral nerves and nociceptors, as do other viruses. Urata recently reported that the olfactory epithelium (which expresses ACE2) is sloughed off for a long time after SARS-CoV-2 infection [13]. Similar to dysosmia, the most reasonable explanation of dysgeusia may be that it is a direct effect of SARS-CoV-2 on the taste buds on the tongue.…”
Section: Discussionmentioning
confidence: 99%